1994
DOI: 10.1007/bf02090360
|View full text |Cite
|
Sign up to set email alerts
|

Does omeprazole (Prilosec) improve respiratory function in asthmatics with gastroesophageal reflux?

Abstract: Gastroesophageal reflux (GER) is common among patients with asthma, and it has been speculated that high GER may exacerbate asthma in some. This study was designed to determine if suppression of acid reflux in patients with asthma would improve pulmonary function. A double-blind, placebo-controlled crossover study design was used to determine the effect of GER suppression with omeprazole (20 mg twice daily) on pulmonary function among asthmatic patients with esophagitis. Four of 15 (27%) asthma patients with G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
62
1
7

Year Published

2000
2000
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 144 publications
(72 citation statements)
references
References 24 publications
1
62
1
7
Order By: Relevance
“…Recently, PPI has been also used for the diagnosis of gastroesophageal reflux, not only in the patients with non-erosive reflux disease (NERD) [28,29] , but also in patients with atypical gastroesophageal reflux symptoms [30,31] . The present study suggests that the four kinds of PPI are effective for the diagnosis of the existence of gastroesophageal acid reflux, and it may be worthwhile investigating whether esomeprazole can shorten the time period necessary for diagnosis.…”
Section: A L T H O U G H T H E S Y M P T O M R E L I E F Wa S F a S Tmentioning
confidence: 99%
“…Recently, PPI has been also used for the diagnosis of gastroesophageal reflux, not only in the patients with non-erosive reflux disease (NERD) [28,29] , but also in patients with atypical gastroesophageal reflux symptoms [30,31] . The present study suggests that the four kinds of PPI are effective for the diagnosis of the existence of gastroesophageal acid reflux, and it may be worthwhile investigating whether esomeprazole can shorten the time period necessary for diagnosis.…”
Section: A L T H O U G H T H E S Y M P T O M R E L I E F Wa S F a S Tmentioning
confidence: 99%
“…Asthma symptoms also correlated with esophageal pH events on 24-h esophageal pH monitoring [11] . Previous studies on the effect of antireflux therapy on asthma have shown inconsistent results [12][13][14][15][16][17][18][19][20][21][22][23][24] . Most of these studies have been done in small groups of patients with different proton-pump inhibitors and were done for short durations of anti-reflux therapy.…”
Section: Introductionmentioning
confidence: 99%
“…There have been many studies dealing with asthma outcome and medical anti-reflux therapy. Field and Sutherland (1998) reviewed the previously published data on medical anti-reflux therapy with H 2 -receptor blockers (H 2 blockers), cimetidine (Goodall et al 1981;Larrain et al 1991) and ranitidine (Harper et al 1987;Nagel et al 1988;Ekstrom et al 1989;Gustaffson et al 1992), and with a proton pump inhibitor (PPI) omeprazole (Ford et al 1994;Meier et al 1994;Harding et al 1996;Teichtahl et al 1996), showing that asthma symptoms were improved. Kiljander (2003) suggested that, in the management of GERD-related asthma, PPIs other than omeprazole should be used at double the standard dose.…”
mentioning
confidence: 99%